Assessment of the antibacterial, cytotoxic and mutagenic potential of the phenolic-rich hydroalcoholic extract from Copaifera trapezifolia Hayne leaves - Leandro, Luis Fernando; Moraes, Thais da Silva; Oliveira, Pollyanna Francielli de; Alves, Jacqueline Morais; Senedese, Juliana Marques; Ozelin, Saulo Duarte; Resende, Flavia Aparecida [UNESP]; De Grandis, Rone Aparecido [UNESP]; Varanda, Eliana Aparecida [UNESP]; Bastos, Jairo Kenupp; Tavares, Denise Crispim; Gomes Martins, Carlos Henrique (Microbiology Soc, 2016)
Copaifera trapezifolia Hayne occurs in the Atlantic Rainforest, which is considered one of the most important and endangered tropical forests on the planet. Although literature works have described many Copaifera spp., their biological activities remain little known. In the present study, we aimed to evaluate (1) the potential of the hydroalcoholic extract from C. trapezifolia leaves (CTE) to act against the causative agents of tooth decay and apical periodontitis and (2) the cytotoxicity and mutagenicity of CTE to ensure that it is safe for subsequent application. Concerning the tested bacteria, the MIC and the minimum bactericidal concentration of CTE varied between 100 and 400 mu g ml(-1). The time-kill assay conducted at a CTE concentration of 100 mu g ml(-1) evidenced bactericidal activity against Porphyromonas gingivalis (ATCC 33277) and Peptostreptococcus micros (clinical isolate) within 72 h. CTE at 200 mu g ml(-1) inhibited Porphyromonas gingivalis and Peptostreptococcus micros biofilm formation by at least 50 %. A combination of CTE with chlorhexidine dichlorohydrate did not prompt any synergistic effects. The colony-forming assay conducted on V79 cells showed that CTE was cytotoxic at concentrations above 156 mu g ml(-1). CTE exerted mutagenic effect on V79 cells, but the micronucleus test conducted on Swiss mice and the Ames test did not reveal any mutagenicity. Therefore, the use of standardized and safe extracts could be an important strategy to develop novel oral care products with antibacterial action. These extracts could also serve as a source of compounds for the discovery of new promising biomolecules.